Exciting the Body Sensoriality and Capitalism in Modern Culture - Hernández Barbosa, Sonsoles (Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2024)
XIII, 241 p. 23 illus., 22 illus. in color.